Factors That Influence Customer Loyalty: Brand Image, Brand Awareness, And Experiential Marketing: Study Of Bank Muamalat Customers, Malang City - Sofi Adawiyah; Irmayanti Hasan (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study examines the impact of brand image, brand awareness, and experiential marketing on customer loyalty at Bank Muamalat in Malang City. This study employed a quantitative methodology, utilizing data gathered via questionnaires administered to active clients of Bank Muamalat. Respondents were chosen through a non-probability sampling approach based on the following criteria: a minimum age of 17 years, a customer tenure of six months or more, and possession of products from Bank Muamalat. The questionnaire comprised 26 statement questions and included a total sample of 130 respondents. Data were examined via multiple linear regression through SPSS software. The findings indicated that brand awareness and experience marketing significantly affect client loyalty. This research suggests that customer awareness of the Bank Muamalat brand's presence and principles directly impacts their loyalty decisions. Moreover, favorable client experiences with banking services, including effective staff contacts, seamless digital services, and alignment with Sharia principles, are essential in fostering loyalty. Conversely, brand image exerts little impact on client loyalty. This condition suggests that while Bank Muamalat's brand image is perceived favorably by clients, more than this aspect is needed to directly affect customer involvement with the bank. The regression model employed in this study exhibits an R Square value of 63.8%, signifying that the variables of brand image, brand awareness, and experiential marketing collectively account for most of the variability in consumer loyalty. Nonetheless, the remaining 36.2% is affected by additional factors not encompassed in this study, like service quality, pricing, or emotional influences. This study offers strategic insights for Bank Muamalat and other Islamic banks in comprehending consumer behavior. Strategies to enhance customer loyalty should concentrate on bolstering brand awareness and fostering great consumer experiences, both online and through direct engagement. A more comprehensive approach is required to enhance the influence of brand image as a determinant of consumer loyalty. Consequently, the findings of this study can serve as a foundation for formulating more efficacious marketing and service strategies to enhance client loyalty within the Islamic banking sector.